Characterization of a single electrode focusing lens for ion beam deceleration - Lopes, Jose (2017)
An ion beam deceleration system was studied for the highcurrent ion implanter at the Laboratório de Aceleradores e Tecnologias de Radiação at the Campus Tecnológico e Nuclear, of Instituto Superior Técnico. The installed system consists of a target plate and one electrostatic focusing lens with one electrode. This article describes the results of the evaluation of the new system. With this upgrade, the ion implanter provides enhanced versatility for decelerating to 5 keV a high current ion beam at the µA level. This implantation provides a wide area and allows for a continuous magnetic beam scanning, extending the energy range to lower values, opening up a wider set of applications.